ANALISIS SISWA SMA LABORATORIUM UM YANG BERWIRAUSAHA DITINJAU DARI PENGETAHUAN KEWIRAUSAHAAN, PENDIDIKAN EKONOMI KELUARGA, DAN MINAT BERWIRAUSAHA - Dwi rahmawati agustia (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2018)
Students are not shy anymore in entrepreneurship either online or offline. The type of this research is qualitative research with phenomenology approach. Students who became the subject in this study amounted to 7 students. The results of student test entrepreneurship into the category very good. Entrepreneurship knowledge, family economic education, and entrepreneurship interest provide students motivation in entrepreneurship. Suggestions in this study entrepreneurial students to better deepen knowledge of entrepreneurship well, family economic education is more applied again, and entrepreneurial interest is more improved again.Keywords: Entrepreneurial Knowledge, Family Economic Education, and Entrepreneurship Interests